Identification and estimation of preference distributions when voters are ideological - Antonio Merlo; Áureo de Paula (Centre for Microdata Methods and Practice (cemmap), 2015)
This paper studies the nonparametric identification and estimation of voters' preferences when voters are ideological. We establish that voter preference distributions and other parameters of interest can be identified from aggregate electoral data. We also show that these objects can be consistently estimated and illustrate our analysis by performing an actual estimation using data from the 1999 European Parliament elections.
Keywords: D72; C14; 330; Voting; Voronoi tessellation; identification; nonparametric